Development of the vocational home economics program in Arkansas from 1917 to 1939 - Williams, Kate, author; Morgan, David H., advisor; Williamson, Maude, committee member; Elliff, Rowan E., committee member; Holman, Mary V., committee member; Burnham, Helen A., committee member (Colorado State University. Libraries, 1941)
To view the abstract, please see the full text of the document.
Keywords: Home economics -- Arkansas; Home economics -- Study and teaching